2000
DOI: 10.1002/1097-0290(20010205)72:3<315::aid-bit8>3.0.co;2-g
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic model of in vivo folding and inclusion body formation in recombinantEscherichia coli

Abstract: Aggregation of misfolded proteins can reduce the yield in recombinant protein production. The underlying complex processes are additionally influenced by cellular physiology. Nevertheless, a lumped‐parameter model of kinetic competition between folding and aggregation was sufficient to track properly the specific concentration of a human protein produced in E. coli and its partitioning into soluble and insoluble cell fractions. Accurate estimation of the protein‐specific parameters required informative experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 41 publications
1
12
0
Order By: Relevance
“…In vitro studies on protein aggregation indicated variability in the mechanisms of aggregation even for a given protein [8]. Kinetic analysis of in vitro protein aggregation [8][9][10] but also in vivo monitoring of IB formation [11] revealed that aggregate formation can be described as a pseudo-first-order process. There are two possible mechanisms for IB formation, either IBs start growing from single or limited number of molecules acting as nucleation site or from smaller aggregates which assemble and form larger aggregates [12] .…”
Section: Cellular Formation Of Ibsmentioning
confidence: 99%
“…In vitro studies on protein aggregation indicated variability in the mechanisms of aggregation even for a given protein [8]. Kinetic analysis of in vitro protein aggregation [8][9][10] but also in vivo monitoring of IB formation [11] revealed that aggregate formation can be described as a pseudo-first-order process. There are two possible mechanisms for IB formation, either IBs start growing from single or limited number of molecules acting as nucleation site or from smaller aggregates which assemble and form larger aggregates [12] .…”
Section: Cellular Formation Of Ibsmentioning
confidence: 99%
“…DISCUSSION Fig. 1 shows a simplified scheme describing the conformational opportunities for a protein such as HypF-N after biosynthesis in a bacterial cell (3,43). The protein is synthesized and released from the ribosome as an unfolded polypeptide chain.…”
Section: Evaluation Of the Stabilities And Aggregation Propensities Omentioning
confidence: 99%
“…The first early event of aggregation of HypF-N, which also occurs from the partially folded state, is also relatively rapid and takes place within 5 s (35,42). Changes of protein concentrations in an E. coli cell as a result of biosynthesis and degradation occur much more slowly, on the time scale of hours (43). This implies that although the total amount of HypF-N within a cell changes with time after induction of expression, the native, unfolded, partially folded, and initial aggregated states are in constant dynamic equilibrium.…”
Section: Evaluation Of the Stabilities And Aggregation Propensities Omentioning
confidence: 99%
“…Accumulation of soluble hFGF-2 starts with a delay after heatshock protein synthesis reached their peak level (Hoffmann and Rinas, 2000). Modelling data indicate that the soluble state might be reached only after in vivo refolding from the aggregated state (Hoffmann et al, 2001).…”
Section: Introductionmentioning
confidence: 99%